Effects of Menstrual Cycle Phase and Stress on Spatial Navigational Strategy Use - McHale, Alexandra Lauren (Department of Psychology, 2020)
Previous research suggests there are significant effects on spatial navigation of menstrual cycle phase and, independently, of stress exposure. However, no published study explores how these variables might interact to affect human navigational strategies. Such exploration is important because women experience stressful events throughout the menstrual cycle. Hence, the primary aim of the research described here was to investigate the potentially interacting effect of menstrual cycle phase and acute psychosocial stress on allocentric (i.e., relying on a cognitive map of the environment, created using distal cues), egocentricresponse (i.e., relying on body-turn directions), and egocentric-cue (i.e., relying on the location of specific proximal cues) navigation. The study tested three hypotheses: (1) menstrual cycle phase will significantly affect navigational strategy (women in the early follicular and ovulatory phases will prefer egocentric strategies, whereas those in the mid/late luteal phase will prefer an allocentric strategy); (2) stress will significantly affect navigational strategy (women exposed to an acute psychosocial stressor will prefer egocentric strategies while those unexposed will prefer an allocentric strategy); and (3) there will be a significant interaction effect on navigational strategies (particularly, women in the mid/late luteal phase will use egocentric strategies when stressed and allocentric strategies when not). Naturallycycling young adult women (N = 60), each in either the early follicular, ovulatory, or mid/late luteal phase of the cycle, were randomly assigned to either a stress-exposure condition (the Paced Auditory Serial Addition Task [PASAT], which required them to rapidly add pairs of verbally presented digits at increasing between-digit intervals) or an equivalent control condition (the un-PASAT, which required them to add pairs of digits at a constant, slower, between-digit speed). Hence, the study groups were: Early Follicular+Stress (n = 11), Early Follicular+Non-Stress (n = 10), Ovulatory+Stress (n = 8), Ovulatory+Non-Stress (n = 8), Mid/Late Luteal+Stress (n = 12), and Mid/Late Luteal+Non-Stress (n = 11). After the manipulation, they completed the Hex Maze, a virtual environment navigation task. The task comprises 10 trial pairs. On the first trial of a pair, participants learn a target platform's location. On the second, they must navigate back to that location. This latter trial can be completed using either an allocentric, egocentric-response, or egocentric-cue strategy. Results suggested that the PASAT successfully induced psychological and physiological stress. A mixed linear model analysis detected, with regard to the navigational strategy outcome variables, no significant main effect of menstrual cycle phase (a result inconsistent with previous research), no significant main effect of stress exposure (a result consistent with some prior research), and no significant interaction effect. Although the interaction was non- significant, trends within the data suggested the results followed the predicted direction. Hence, this relatively small-scale study may serve as a foundation for future research as it provides valuable hypothesis-generating insight into the possible interaction of menstrual cycle phase and stress, and encourages the further investigation of this topic.